2005
DOI: 10.1038/ng1673
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune-associated lymphoid tyrosine phosphatase is a gain-of-function variant

Abstract: A SNP in the gene PTPN22 is associated with type 1 diabetes, rheumatoid arthritis, lupus, Graves thyroiditis, Addison disease and other autoimmune disorders. T cells from carriers of the predisposing allele produce less interleukin-2 upon TCR stimulation, and the encoded phosphatase has higher catalytic activity and is a more potent negative regulator of T lymphocyte activation. We conclude that the autoimmune-predisposing allele is a gain-of-function mutant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
600
2
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 645 publications
(637 citation statements)
references
References 14 publications
27
600
2
8
Order By: Relevance
“…For example in PTPN22, the minor allele of the R620W SNP is associated with greater risk of developing RA, JIA, T1D and SLE but is protective for Crohn's disease. 24,25 There is also emerging data suggesting that one of the associated SNPs at the IL2RA locus confers differing risk and protective effects for T1D and multiple sclerosis. 26,27 JIA is a phenotypically heterogeneous disease and can be classified into more clinically homogeneous diseases using the ILAR classification criteria (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…For example in PTPN22, the minor allele of the R620W SNP is associated with greater risk of developing RA, JIA, T1D and SLE but is protective for Crohn's disease. 24,25 There is also emerging data suggesting that one of the associated SNPs at the IL2RA locus confers differing risk and protective effects for T1D and multiple sclerosis. 26,27 JIA is a phenotypically heterogeneous disease and can be classified into more clinically homogeneous diseases using the ILAR classification criteria (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, another study indicates that in carriers of the PTPN22 T allele, 1730 VAN DER HELM-VAN MIL ET AL the intrinsic phosphatase activity is increased, revealing a gain of function (36). These authors suggested that the paradoxical findings might be explained by a less sufficient activity of T regulatory cells in the presence of the PTPN22 T allele (36). Moreover, PTPN22 is expressed not only on T cells but also on B cells, natural killer cells, and macrophages (where its function is unknown), indicating that the action of PTPN22, in addition to its capacity to modulate T cell receptor signaling, might also be routed through manipulation of other aspects of the immune system.…”
Section: Risk Factors For Acpa-positive Ramentioning
confidence: 92%
“…In contrast, another study indicates that in carriers of the PTPN22 T allele, 1730 VAN DER HELM-VAN MIL ET AL the intrinsic phosphatase activity is increased, revealing a gain of function (36). These authors suggested that the paradoxical findings might be explained by a less sufficient activity of T regulatory cells in the presence of the PTPN22 T allele (36).…”
Section: Risk Factors For Acpa-positive Ramentioning
confidence: 97%
“…They showed that B‐cells from carriers of this PTPN22 risk allele contained high frequencies of autoreactive clones compared with those from non‐carriers showing how a single polymorphism at one genetic locus can affect the B‐cell repertoire 61. This PTPN22 polymorphism is a gain‐of‐function variant leading to reduced B‐ and T‐cell receptor signalling,62, 63 and has been associated with a range of autoimmune diseases, including RA,64, 65 type 1 diabetes66 and SLE 67. Similar studies on variation in other genes are likely to provide further useful information on how specific biological pathways regulate the B‐cell repertoire.…”
Section: Slementioning
confidence: 99%